GEO 600 and the GEO-HF upgrade program: successes and challenges. (7th March 2016) - Dooley, K L; Leong, J R; Adams, T; Affeldt, C; Bisht, A; Bogan, C; Degallaix, J; Gräf, C; Hild, S; Hough, J; Khalaidovski, A; Lastzka, N; et al.
Abstract: The German–British laser-interferometric gravitational wave detector GEO 600 is in its 14th year of operation since its first lock in 2001. After GEO 600 participated in science runs with other first-generation detectors, a program known as GEO-HF began in 2009. The goal was to improve the detector sensitivity at high frequencies, around 1 kHz and above, with technologically advanced yet minimally invasive upgrades. Simultaneously, the detector would record science quality data in between commissioning activities. As of early 2014, all of the planned upgrades have been carried out and sensitivity improvements of up to a factor of four at the high-frequency end of the observation band have been achieved. Besides science data collection, an experimental program is ongoing with the goal to further improve the sensitivity and evaluate future detector technologies. We summarize the results of the GEO-HF program to date and discuss its successes and challenges.